Does hyperthermic preconditioning affect the rate of surgical site infection rate and inflammatory reaction in colorectal cancer patients? A prospective randomized clinical trial - (:unkn) unknown (TURKISH SURGICAL ASSOC, 2018)
Objective: Hyperthermic preconditioning has been shown to protect against different insults in experimental studies. However, clinical studies assessing its effects remain limited, The aim of this study was to investigate the effects of hyperthermic preconditioning on the rate of surgical site infection and inflammatory reaction in patients undergoing elective colorectal cancer surgery. Material and methods: Patients with colorectal cancer, scheduled to undergo elective surgery were enrolled in this prospective randomized study. Patients were randomly assigned to either the hyperthermic preconditioning group or control group. Postoperative superficial and deep surgical site infection were recorded. Blood samples were collected from all the patients in the hyperthermic preconditioning group prior to the application of hyperthermia 12 h before surgery, immediately prior to surgery, and 4 h and 24 h postoperatively, For the control group, blood samples were obtained within the same periods without the application of hyperthermia. Levels of interleukin-1, IL-6, and tumor necrosis factor-alpha were measured from blood samples, Results: Twenty patients were randomized to the hyperthermic preconditioning group and 21 to the control group. No significant difference was found in deep or superficial surgical site infection between the groups. No significant difference in the tumor necrosis factor-alpha, interleukm-1, and IL-6 levels was found in serum samples collected before hyperthermia, during the operation, and postoperatively, Conclusion: This study showed that hyperthermic preconditioning has no effect on the surgical site infection and cytokine response in patients undergoing elective surgical intervention for colorectal cancer.
Keywords: Colorectal cancer; hyperthermic preconditioning; inflammatory reaction; surgical infection; SHOCK-PROTEIN INDUCTION; FEVER; ISCHEMIA; SEPSIS; SURVIVAL; INJURY; HSP70